Birth of the chaordic age - Hock, Dee, 1929- (Berrett-Koehler Publishers, 1999)
"The worldwide success of VISA International, Dee Hock asserts, is due to its chaordic structure: it is owned by 22,000 member banks, which both compete with each other for 750 million customers and must cooperate by honoring one another's $1.25 trillion in transactions annually across borders and currencies. Birth of the Chaordic Age is the story of how that structure came into being."--Jacket